SIMULTANEOUS ANALYSIS OF ECONOMIC GROWTH AND UNEMPLOYMENT IN INDONESIA - Jolianis, Jolianis; Farlis, Fiko; Sari, Putri (Faculty of Economics and Business, University of Pasundan, 2024)
The research aims is simultaneously analyze economic growth and unemployment. The research object is Indonesia using time series data. The variables being examined in this research are economic growth and unemployment. The exogenous variables are the exchange rate, net export, inflation, foreign direct investment, and population. This research has shown that: 1) inflation and exchange rates have a significant influence on economic growth. A depreciation of the native currency versus foreign currencies will lead to a contraction in economic growth, whereas higher inflation rates in a nation would result in a decline in economic growth. 2) Both population and direct investment influence unemployment. Increased foreign direct investment has the potential to decrease unemployment rates, whereas a greater population might lead to an increase in unemployment. This research examines economic growth and unemployment simultaneously from an economic law perspective.